Analyzing the role of family support, coping strategies and social support in improving the mental health of students: Evidence from post COVID-19 - Yang, Chunying; Gao, Hong; Li, Yuxiang; Wang, Enguo; Wang, Nina; Wang, Qinglei (Frontiers in Psychology, 2022)
Background: The COVID-19 pandemic and the multifaceted response strategies to curb its spread both have devastating effects on mental and emotional health. Social distancing, and self-isolation have impacted the lives of students. These impacts need to be identified, studied, and handled to ensure the well-being of the individuals, particularly the students. This study aims to analyze the role of coping strategies, family support, and social support in improving the mental health of the students by collecting evidence from post covid 19. Methods: Data was collected from the students studying in Chinese universities. A survey questionnaire was designed to collect data form 210 students. Descriptive statistics were calculated using SPSS 21 while hypothesis testing was carried out using Mplus 7. Results: The results demonstrated that family support was strongly positively linked to mental health (β= 0.236, p=0.00) and predicted coping strategies (β=0.520, p=0.00). The direct relationship analysis showed that coping strategy strongly predicted mental health (β=0.534, p-value 0.000). Furthermore, coping strategies were positive and significant at 0.05 thus, significantly mediating the relationship between family support and mental health. STDYX of SIE (specific indirect effect) was (β=0.301, p=0.00), 95% confidence interval CI [0.154–0.148]. The direct effect of family support on mental health was β=0.183 (p=0.02), the direct effect of moderating variable PSS(perceived social support) on mental health was β=0.160 (p=0.054) and the interaction effect of PSSXFS (moderating variable * IV) was β=0.147 (p=0.228) with a 95% CI [-.054—349]. The direct effect of FS(family support) on COP(coping strategies) was β=0.263 (p=0.00), 95% CI [0.135–0.391] , the direct effect of moderating variable PSS on COP was β=0.695 (p=0.00), [95% CI 0.536–0.855] and the interaction effect of FSXPSS (moderating variable * IV) was β=0.357 (0.002) ，95% CI 0.171–0.544] Conclusion: Family support and coping strategies positively predicted mental health, whereas, family support was also found to be positively associated with coping strategies. Coping strategies mediated the positive association between family support and mental health. However, perceived family & other support only moderated the relationship between family support and coping strategies.